Nanoparticle-based microextraction techniques in bioanalysis. (November 2011) - Lasarte-Aragonés, Guillermo; Lucena, Rafael; Cárdenas, Soledad; Valcárcel, Miguel
Nanoparticles (NPs) have attracted a great deal of attention in the last decade due to their exceptional mechanical, optical and electronic properties. This article deals with the use of NPs as probes for the extraction of biomolecules from biological samples. In this context, NPs present some advantages compared with conventional sorbents. Their high surface-to-volume ratio, easy synthetic (especially for inorganic NPs) and derivatization procedures, and their biocompatibility make them a powerful alternative. In order to provide a systematic approach to the topic, NPs have been divided into two general groups attending to their chemical nature. Carbon-based (e.g., fullerene and nanotubes) and inorganic NPs (e.g., gold and magnetic NPs) are considered in depth, explaining their main properties and applications. After these critical considerations, the most important conclusions and essential trends in this field are also outlined.